2006
DOI: 10.1242/dev.02428
|View full text |Cite
|
Sign up to set email alerts
|

Neverland is an evolutionally conserved Rieske-domain protein that is essential for ecdysone synthesis and insect growth

Abstract: Steroid hormones mediate a wide variety of developmental and physiological events in multicellular organisms. During larval and pupal stages of insects, the principal steroid hormone is ecdysone, which is synthesized in the prothoracic gland (PG) and plays a central role in the control of development. Although many studies have revealed the biochemical features of ecdysone synthesis in the PG, many aspects of this pathway have remained unclear at the molecular level. We describe the neverland (nvd) gene, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
189
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(199 citation statements)
references
References 70 publications
7
189
0
3
Order By: Relevance
“…This may be a consequence of the lack of data from genome-wide analyses for the ring gland, coupled to the fact that the characterization of differential patterns of gene expression in the ring gland has been impaired by the small size of this organ (Niwa et al, 2004). Most of the genes that were shown to be expressed in the ring gland are related to the ecdysone biosynthetic pathway (Freeman et al, 1999;Gaziova et al, 2004;Gilbert, 2004;Neubueser et al, 2005;Warren et al, 2001;Yoshiyama et al, 2006), and were not identified in our analysis. Because in transgenesis the pattern of BhC4-1-lacZ expression driven by the 67 bp (2253/2187) fragment is distinct from the expression pattern of the genes that participate in ecdysone biosynthesis, it is possible that our study has revealed a hitherto uncharacterized set of genes which are coexpressed in the ring gland of late embryos.…”
Section: The Bioinformatics Analysis Identified Conserved Cis-regulatmentioning
confidence: 86%
See 1 more Smart Citation
“…This may be a consequence of the lack of data from genome-wide analyses for the ring gland, coupled to the fact that the characterization of differential patterns of gene expression in the ring gland has been impaired by the small size of this organ (Niwa et al, 2004). Most of the genes that were shown to be expressed in the ring gland are related to the ecdysone biosynthetic pathway (Freeman et al, 1999;Gaziova et al, 2004;Gilbert, 2004;Neubueser et al, 2005;Warren et al, 2001;Yoshiyama et al, 2006), and were not identified in our analysis. Because in transgenesis the pattern of BhC4-1-lacZ expression driven by the 67 bp (2253/2187) fragment is distinct from the expression pattern of the genes that participate in ecdysone biosynthesis, it is possible that our study has revealed a hitherto uncharacterized set of genes which are coexpressed in the ring gland of late embryos.…”
Section: The Bioinformatics Analysis Identified Conserved Cis-regulatmentioning
confidence: 86%
“…The molting defective (mld) (Neubueser et al, 2005) and without children (woc) (Warren et al, 2001) genes encode putative transcription factors that are expressed in the ring gland and several other tissues throughout development, for which the target genes have not been identified. The Drosophila genes, such as dare (Freeman et al, 1999), disembodied (dib), shadow (sad) (Gilbert, 2004), ecdysoneless (ecd1) (Gaziova et al, 2004), and neverland (nvd) (Yoshiyama et al, 2006), are all involved in ecdysteroids biosynthesis and are expressed both in the larval ring gland and in adult ovaries, which is the adult source of ecdysteroids. To our knowledge, the BhC4-1 67 bp ring gland enhancer is the only enhancer so far identified, which is able to drive developmentally regulated gene expression solely in the ring gland.…”
Section: The Bhc4-1 Promoter Region Contains Both a Ring Gland And A mentioning
confidence: 99%
“…Pearson's correlation coefficient between the different parameters analyzed in this study (hepatopancreas biomass expressed as hepatosomatic index -HIS, total lipid content -TL and reproductive performance expressed as relative fecundity -RF and hatching rate -HR) and gene expression in the hepatopancreas from spawned Penaeus monodon females (stage 0). conserved Rieske-domain protein essential for ecdysone synthesis and insect growth 267 while involved in cholesterol trafficking (Yoshiyama et al, 2006). 268 15 In previous studies it has been proved that wild broodstock presented better 269 reproductive performance than domesticated animals (Arnold et al, 2013, Coman et al, 270 2013, Marsden et al, 2013.…”
Section: Pmmentioning
confidence: 99%
“…[3][4][5] The abundance of transcripts of the P450 genes has been shown generally to correlate well with basal PG activity and thus with the hemolymph ecdysteroid titer during larval development in a few insects. 6,7) These reports clearly suggest that the transcript levels of these ecdysteroidogenic enzymes are the critical determinants of basal PG activity, and that the regulators of P450 gene expression are key players in the regulation of insect development.…”
mentioning
confidence: 99%